Ceramsite prepared by using overhauled slag, sludge and industrial solid waste and preparation method thereof
Patent Information
- Application Number
- CN202611069086.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的目的在于提供一种利用大修渣复配污泥及工业固废烧制的陶粒及其制备方法,以解决现有技术中原料适应性差、有害元素控制难、资源化效率低的问题
(1)本发明实现了有害元素高效固化,氟主要以不溶性CaF2形式存在于大修渣中,在高温下与磷石膏释放的CaO及微量P2O5反应,生成稳定的Ca5(PO4)3F,氟浸出浓度<100mg/L,符合GB 5085.3-2007及相关行业应用标准要求;重金属(如Pb、Zn、Cr等)在高温下氧化为氧化物或进入硅酸盐晶格,以玻璃体包裹形式实现稳定固化,浸出毒性达标。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste resource utilization technology, specifically relating to a method for preparing ceramsite by combining sludge from major repairs with industrial solid waste. Background Technology
[0002] Spent potlining (SPL) is a hazardous solid waste generated during aluminum electrolysis production. It is highly alkaline and contains fluorides, cyanides, and various heavy metals, exhibiting significant leaching toxicity. It has been listed as HW48 in the National Hazardous Waste List. Currently, safe landfill is the primary method for disposing of SPL; however, this method is not only costly but also results in a potential waste of resources. In recent years, using SPL as a raw material for the resource utilization of building materials has become a research hotspot. However, due to the difficulty in effectively controlling the migration behavior of fluorine and heavy metals at high temperatures, coupled with the large fluctuations in raw material composition, large-scale and stable engineering applications are difficult to achieve.
[0003] Among the various industrial solid wastes co-processed, municipal sludge contains a certain amount of organic matter, which can provide calorific value and form a porous structure during sintering; phosphogypsum, as a by-product of wet-process phosphoric acid production, is mainly composed of calcium sulfate dihydrate (CaSO4·2H2O), which can decompose to produce gas and release calcium oxide (CaO) at high temperatures, and has both foaming and mineralization functions; high-calcium fly ash is a silica-alumina cementitious material, rich in CaO, SiO2, and Al2O3, and has certain pozzolanic activity, which can participate in high-temperature phase reconstruction.
[0004] However, existing resource utilization technologies based on overhaul slag generally suffer from problems such as insufficient process stability, difficulty in pollutant control, and difficulty in achieving high-value and large-scale synergistic utilization. For example, Chinese patent CN121847079A discloses a method for removing heavy metals and fluorides using electrolytic aluminum overhaul slag and red mud as raw materials and employing an acid-alkali washing composite process. Although this process is effective for Cu... 2+ Pb 2+While effective in removing heavy metals and fluorides, the process is lengthy, consumes large quantities of reagents and carriers, and has high overall disposal costs, making it unsuitable for large-scale hazardous waste resource utilization engineering applications. Chinese patent CN113173777A discloses a method for preparing ceramsite directly from overhaul slag, encapsulating and solidifying fluorides within the glassy body of the ceramsite to meet conventional performance requirements. However, this method lacks pre-treatment with water washing of the overhaul slag, failing to remove soluble fluoride, free alkali, and readily soluble salts from the raw materials beforehand. This leads to easy volatilization of fluorides and accumulation of alkaline components in the kiln during sintering, increasing the load on exhaust gas treatment and causing defects such as cracking, pores, and surface crumbling in the ceramsite product. Furthermore, soluble fluoride is difficult to completely mineralize and fix during sintering, posing a risk of long-term excessive leaching and secondary pollution. In addition, this patent lacks precise classification, particle size grading, and structural gradient design for the overhaul slag, and the raw material pretreatment lacks specificity, making it difficult to ensure uniform dispersion and scientific compatibility of various elements. Chinese patent CN121672962A discloses a method for decomposing cyanide by calcining lithium extraction residue with a calcium-based fluoride-fixing agent after compounding with overhaul slag. This method achieves fluoride fixation by generating CaF2 precipitate. However, due to the high solubility of CaF2, it is easy to release fluoride ions again under acid and alkaline leaching conditions, which can only achieve short-term physical fluoride fixation and lacks long-term solidification stability. This patent also fails to classify overhaul slag, control its particle size, or design a core-shell structure for granulation, making it difficult to achieve precise proportions and directional mineralization reactions of calcium, phosphorus, and fluorine elements.
[0005] In summary, existing technologies still have significant shortcomings in terms of the fineness of raw material pretreatment, the long-term stability of the solid fluoride mechanism, the degree of synergy of multi-source solid waste, and the uniformity of products. There is an urgent need to develop a ceramsite formulation and preparation process that has strong pretreatment targeting, stable solid fluoride mineral phase, and can realize the high-value synergistic utilization of multiple solid wastes. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing ceramsite by calcining sludge and industrial solid waste using overhaul slag, in order to solve the problems of poor raw material adaptability, difficulty in controlling harmful elements, and low resource utilization efficiency in the prior art.
[0007] To achieve the above objectives, the present invention employs the following:
[0008] A type of ceramsite produced by calcining slag, sludge, and industrial solid waste from major repairs, is composed of the following raw materials by weight percentage: After water washing, the first type of major repair slag is 8%~15%, the second type of major repair slag after water washing is 15%~25%, municipal sludge is 20%~35%, phosphogypsum is 5%~8%, and high-calcium fly ash is 10%~20%; The molar ratio of calcium, phosphorus, and fluorine in the raw material system is controlled as Ca:P:F = (15~20):2:1.
[0009] Preferably, the ceramsite has a core-shell structure, wherein the core is a second type of overhaul slag particle after water washing, and the shell is a sintered dense layer containing a chemically mineralized solid fluorine phase and a glassy physical encapsulation phase composed of fluorapatite (Ca5(PO4)3F).
[0010] Preferably, the first type of overhaul slag after water washing is cathode carbon block edge material and / or ramming material, with a particle size ≤0.1mm, calorific value ≥1000 kcal / kg, total fluorine ≤0.5%, soluble fluorine ≤0.1%, and cyanide ≤5 mg / L; The second type of overhaul slag after water washing is an impermeable material and / or refractory brick, with a particle size of 0.5~2 mm, total fluorine ≤0.8%, and dissolved fluorine ≤0.2%; The particle size of the municipal sludge is ≤0.15 mm; The particle size of the phosphogypsum is ≤0.075 mm; The high-calcium fly ash contains ≥20% calcium oxide (CaO) and has a particle size ≤0.075 mm.
[0011] Preferably, the ceramsite meets the following performance indicators: Bulk density is 500~700 kg / m³ 3 , Cylinder compressive strength ≥1.0 MPa The water absorption rate is 8%~15%; Its fluoride leaching concentration (in F) - The leaching concentration of heavy metals meets the requirements of the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB 5085.3-2007). The leaching concentration of heavy metals is ≤5 mg / L, the leaching concentration of cyanide is ≤0.5 mg / L, and the leaching concentration of heavy metals meets the requirements of the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (
[0012] This invention further protects a method for preparing ceramsite by calcining compound sludge and industrial solid waste from overhaul slag, comprising the following steps: S1. Preparation of matrix powder: Weigh the first type of major repair slag after water washing, municipal sludge, phosphogypsum and high calcium fly ash according to the ratio, mix and homogenize them to obtain matrix powder; S2, Core-shell gradient granulation: Using the second type of overhaul slag particles after water washing as the core, after wetting with water spray, the matrix powder obtained in step S1 is added to the rolling granulator, so that the matrix powder coats the surface of the core to form green pellets with a core-shell structure, and dried to a moisture content ≤3%; S3. High-temperature sintering: The green pellets dried in step S2 are sent into a kiln and subjected to thermal treatment in sequence through a preheating section, a medium-temperature reaction section, a high-temperature sintering section and a cooling section to obtain the ceramsite.
[0013] Preferably, in step S1, the moisture content of the matrix powder is controlled as follows: 12%~15% in summer and 15%~18% in winter; the mixing and homogenization time is 10~15 min.
[0014] Preferably, in step S2, the particle size of the green pellets is 6~12 mm; the drying operation adopts a mesh belt dryer, with two-stage temperature control: the first stage is dried at 105 ℃ for 25 min, and the second stage is dried at 120 ℃ until the moisture content is ≤2.5%.
[0015] Preferably, in step S3: The preheating section heats up to 100-300°C at a rate of 5-8°C / min to slowly remove water of crystallization and organic matter, preventing premature volatilization of fluorine. The intermediate-temperature reaction section involves oxidation at 600–900 °C for 40–60 min to promote Ca oxidation. 2+ and Combined, a fluorapatite precursor is initially generated; The high-temperature sintering section is heated to 1100-1200 ℃ at a rate of 30-40 ℃ / min to form a dense glassy phase, in which fluorapatite is fully crystallized and the fluorine solidification rate is ≥98%. The cooling section involves first slowly cooling the material inside the kiln to 550~600 ℃ at a rate of ≤10 ℃ / min, and then allowing it to be discharged and naturally cooled to room temperature to avoid sudden cooling cracking and shell shedding.
[0016] Preferably, in the high-temperature sintering section, a weak oxidizing atmosphere is used in the kiln, with an oxygen (O2) content of 2% to 5%, to avoid the decomposition and volatilization of fluorides caused by reduction; when the total fluorine content in the raw materials is too high, the firing temperature of the high-temperature sintering section is increased by 30 to 50°C, and the holding time is extended by 5 to 8 minutes.
[0017] Preferably, the method further includes configuring alkali spraying and bag filter equipment at the kiln tail to control fluorine emissions ≤3mg / m³. 3 .
[0018] Compared with the prior art, the present invention provides a method for preparing ceramsite by calcining compound sludge and industrial solid waste using overhaul slag, and has the following beneficial effects: (1) This invention achieves efficient solidification of harmful elements. Fluorine mainly exists in the overhaul slag in the form of insoluble CaF2. At high temperature, it reacts with CaO and trace P2O5 released by phosphogypsum to generate stable Ca5(PO4)3F. The fluorine leaching concentration is <100mg / L, which meets the requirements of GB 5085.3-2007 and related industry application standards. Heavy metals (such as Pb, Zn, Cr, etc.) are oxidized into oxides or enter the silicate lattice at high temperature, and are stably solidified in the form of glass encapsulation, and the leaching toxicity meets the standards.
[0019] 2. This invention realizes the synergistic utilization of multi-source solid waste, and can simultaneously and synergistically treat four typical industrial solid wastes: overhaul slag, municipal sludge, phosphogypsum, and fly ash. The total amount of solid waste mixed in is over 85%, truly realizing "treating waste with waste and turning waste into treasure", significantly reducing raw material costs, and having outstanding environmental and economic benefits.
[0020] 3. This invention features a highly adaptable process, optimizing the washing, segmented temperature control during granulation, gradient sintering, and slow cooling processes. It employs a graded particle size design of "coarse aggregate + fine matrix," ensuring both green pellet strength and promoting firing expansion and uniform pore development. The coarse-particle overhaul slag acts as a skeletal support, preventing granulation collapse and preheating cracking, while the fine-powder matrix facilitates high-temperature liquid phase generation and foaming expansion. This process eliminates the need for expensive deep defluorination pretreatment and energy-intensive grinding, offering simple operation, low energy consumption, and high tolerance, making it suitable for large-scale industrial continuous production.
[0021] 4. The product produced by the process of this invention has stable performance. The ceramsite has a "dense on the outside and sparse on the inside" microstructure, with a dense hard shell on the surface and uniformly interconnected micropores inside. The macroscopic performance indicators are excellent and stable, the particles are round and full, spherical or near-spherical, with good gradation, and the product performance is stable and controllable. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings involved in the embodiments are now briefly described. Obviously, the drawings in the following description are merely illustrative of some embodiments of the present invention. For those skilled in the art, other forms of drawings can be constructed based on these drawings without creative effort.
[0023] Figure 1 This is a flowchart of the overall process for preparing ceramsite using a method proposed in this invention, which involves combining sludge and industrial solid waste from major repair slag. Figure 2 This is a diagram showing the raw material ratio and particle size requirements for ceramsite proposed in this invention; Figure 3 This is a diagram of the ceramsite after firing according to the present invention; Figure 4 This is a microscopic morphology image of the ceramsite after firing according to the present invention; Figure 5 This is a diagram showing the chemical composition of the ceramsite after firing according to the present invention. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Figure 1 A flowchart illustrating the overall process for preparing the ceramsite of this invention is shown. Figure 1 As shown, the first type of overhaul slag, municipal sludge, phosphogypsum and high-calcium fly ash are weighed according to the proportion and then forcibly mixed and homogenized by a twin-shaft mixer to prepare composite matrix powder. Then, the second type of overhaul slag is used as the core, and after spray wetting and activation, it is rolled and granulated to form a dense "core-shell" structure. The moisture content of the mixture is controlled and dried to obtain green pellets. Finally, the green pellets are preheated in a rotary kiln, reacted at medium temperature and sintered at high temperature, and then treated with a kiln tail treatment system with alkali spraying and bag dust collection to obtain the finished lightweight ceramsite.
[0026] This invention provides a method for preparing ceramsite by calcining compound sludge and industrial solid waste using overhaul slag, with the core innovation being: Using aluminum electrolysis overhaul slag as the main raw material, and compounded with municipal sludge, phosphogypsum, and high-calcium fly ash, a four-component formulation is developed. By precisely controlling the composition of the silicon-aluminum-calcium system and the calcium-phosphorus-fluorine molar ratio, multiple functions such as foaming and pore formation, skeleton support, fluorine fixation and weight consolidation, and high-temperature enhancement are achieved simultaneously. At the same time, the overhaul slag is subjected to classification pretreatment and precise particle size control. A core-shell structure gradient granulation method with a "coarse core and fine shell" is adopted, along with multi-stage gradient heating and slow cooling processes. This constructs a dual solidification mechanism of chemical mineralization and fluorine fixation by fluorapatite and physical encapsulation in a glassy body. This fundamentally solves the technical problems of easy fluorine leaching, poor product uniformity, and high risk of long-term leaching of harmful elements in traditional CaF2 precipitation solidification. The ceramsite achieves synergistic compliance with standards for strength, density, water absorption, and harmlessness indicators.
[0027] This invention further leverages the advantages of a multi-solid-waste synergistic system, exploring the complementary functional characteristics of each raw material to achieve synergistic and efficient resource utilization of various solid wastes. The phosphogypsum used in this invention is rich in phosphate and calcium ions, serving as a highly efficient heavy metal solidification component, stabilizing heavy metal ions in overhaul slag in situ. High-calcium fly ash and the iron and aluminum components in the system can form stable phases such as ferrates and aluminates with heavy metals, further enhancing the solidification effect. The phosphate and iron-aluminum active components also contribute to the solidification of Zn. 2+ Cd 2+ Cu 2+ Various heavy metal ions also exhibit excellent solidification properties. By synergistically combining phosphogypsum, high-calcium fly ash, overhaul slag, and municipal sludge, the functional characteristics of each solid waste can be fully utilized, achieving "treating waste with waste and turning waste into treasure." I. Raw Material Formulation System The ceramsite formulation of this invention, by mass percentage, consists of the following components: 8%~15% of first-class major repair slag after water washing, 15%~25% of second-class major repair slag after water washing, 20%~35% of municipal sludge, 5%~8% of phosphogypsum, and 10%~20% of high-calcium fly ash. Simultaneously, the molar ratio of calcium, phosphorus, and fluorine in the raw material system, Ca:P:F = (15~20):2:1, is controlled to ensure the stable formation of fluorapatite.
[0028] Figure 2 The raw material ratio and particle size requirements of the ceramsite of this invention are shown. For example... Figure 2 As shown, there are significant differences in the proportion and particle size of various raw materials: high-calcium fly ash accounts for the highest proportion in the formula, followed by municipal sludge, and the proportions of the second type of overhaul slag, phosphogypsum and the first type of overhaul slag decrease in that order; in terms of particle size requirements, the second type of overhaul slag has the widest particle size range (0.5~2mm), followed by municipal sludge (≤0.15 mm), while the particle size requirements of the other raw materials are more refined (≤0.1 mm or ≤0.075mm) to ensure the synergistic matching of different functional components in the granulation and sintering process.
[0029] The technical requirements and pretreatment specifications for each raw material are as follows: (1) Category I overhaul slag: derived from carbonaceous components such as cathode carbon block scrap and ramming material. A normal temperature countercurrent intermittent water washing process is adopted, with a single soaking of 30-50 min, repeated washing twice, and draining and stockpiling for 48 h for natural dehydration. After washing, the calorific value is ≥1000 kcal / kg, the particle size is ground to ≤0.1 mm, total fluoride (perfluoride) is ≤0.5%, dissolved fluoride is ≤0.1%, cyanide is ≤5 mg / L, and the leaching toxicity meets the requirements of the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB 5085.3-2007).
[0030] (2) Second type of overhaul residue: derived from silica-alumina components such as impermeable materials and refractory bricks. After crushing, it is screened in two stages, and particles with a particle size range of 0.5~2 mm are taken as core aggregate, while the undersized fine powder is included in the shell powder for reuse. The particle size is controlled between 0.5~2 mm, with total fluorine (perfluorine) ≤0.8% and dissolved fluorine ≤0.2%.
[0031] (3) Municipal sludge: After dewatering, the moisture content is ≤80%, after drying, the moisture content is ≤15%, and finally crushed to a particle size ≤0.15 mm. The organic matter in the sludge can provide calorific value supplementation and improve the plasticity of the mixture to facilitate pelleting. Trace elements such as phosphorus (P) and nitrogen (N) can participate in the formation of subsequent mineral phases.
[0032] (4) Phosphogypsum: initial moisture content ≤ 25%, after drying, it is co-ground with high-calcium fly ash for 15~20 min until the particle size ≤ 0.075 mm. Phosphogypsum decomposes at 600~800 ℃ to generate SO2 and O2, and the generated internal pressure promotes the expansion and foaming of the material; the calcium oxide (CaO) produced by decomposition reacts with phosphate (P2O5) and fluoride ion (F - ) in the system to generate fluorapatite (Ca5(PO4)3F), realizing the stable chemical immobilization of fluorine; at the same time, it provides CaO to adjust the alkalinity of the system and participates in the formation of the silicate network structure.
[0033] (5) High-calcium fly ash: mass fraction of calcium oxide (CaO) ≥ 20%, ground to a particle size ≤ 0.075 mm. As a donor of silicon, aluminum and calcium, it can balance the silicon-aluminum-calcium ratio in the system, promote the formation of mineral phases such as calcium silicate and calcium aluminate at high temperature, and its fineness can ensure the reaction activity, facilitate the formation of liquid phase, and be encapsulated and solidified by the vitreous body in the later stage.
[0034] II. Preparation Process The supporting preparation method of the present invention specifically includes the following steps: Step 1: Preparation of Matrix Powder Weigh the first type of overhaul slag after water washing, municipal sludge, phosphogypsum and high-calcium fly ash according to the formula ratio, put them into a double-shaft mixer for forced mixing and homogenization for 10~15 min, until the materials have uniform color and qualified dispersion, so as to obtain the composite matrix powder. Adjust the moisture content of the powder according to the ambient temperature: control it to 12%~15% in summer and 15%~18% in winter.
[0035] Step 2: "Core-Shell" Gradient Pelletization Taking the second type of overhaul slag particles with a particle size of 0.5~2.0 mm as the rigid core, spray atomized water on the surface of the core for wetting and activation, then add the composite matrix powder prepared in Step 1 into a rolling pelletizer, so that the powder is densely coated on the surface of the core to form a green pellet with a "coarse core and fine shell" core-shell structure. During the pelletization process, the moisture content of the mixture is controlled to be 12%~18%. The prepared green pellets are controlled to have a particle size of 6~12 mm, irregular, cracked and unqualified pellets with non-conforming particle sizes are screened out, and the crushed materials and fine particles are returned to the matrix powder batching process for recycling.
[0036] The green pellets are sent to a mesh belt dryer for two-stage temperature-controlled drying: the front stage is dried at 105 ℃ for 25 min, and the rear stage is kept at a constant temperature of 120 ℃ for final treatment, so that the moisture content of the green pellets is finally dried to ≤ 2.5%, avoiding defects such as burst pores and cracking during high-temperature sintering. After drying, screening is performed again to remove cracked, irregular unqualified green pellets, so as to ensure uniform quality of the pellets entering the kiln.
[0037] Step 3: High-temperature Sintering and Crystal Phase Reconstruction The qualified green pellets are fed into the rotary kiln and undergo thermal treatment in sequence through the preheating section, the medium-temperature reaction section, the high-temperature sintering section, and the slow cooling section inside the kiln. Preheating section: The temperature is increased to 100-300 ℃ at a rate of 5-8 ℃ / min to slowly remove water of crystallization and residual organic matter, and to prevent premature volatilization of fluorine.
[0038] Medium-temperature reaction stage: The temperature is raised to 600~900 ℃, and oxidation is maintained at this temperature for 40~60 min. During this stage, phosphogypsum decomposes to produce active CaO, which promotes Ca2+ oxidation. 2+ and The combination initially produces the fluorapatite precursor.
[0039] High-temperature sintering section: The temperature is raised to 1100~1200 ℃ and held for 30~40 min to allow the material to form a dense glassy phase, with complete crystallization of fluorapatite and a fluorine fixation rate ≥98%. A weakly oxidizing atmosphere is maintained throughout the kiln process, controlling the oxygen volume fraction to 2%~5% to avoid the decomposition and volatilization of fluorides caused by a reducing atmosphere. When the perfluorine content of the raw material is high, the firing temperature is increased by 30~50 ℃, and the holding time is correspondingly extended by 5~8 min.
[0040] Slow cooling section: After high-temperature sintering, the ceramsite is slowly cooled to 550~600 ℃ in the kiln at a cooling rate of ≤10 ℃ / min, and then naturally cooled to room temperature after exiting the kiln, in order to avoid cracking and shell peeling caused by sudden cooling.
[0041] III. Exhaust Gas Treatment and Quality Control The rotary kiln tail must be equipped with alkaline spraying (NaOH / Ca(OH)2 solution) and bag filter dust collection devices to control the fluorine emission concentration to ≤3 mg / m³. 3 At the same time, it is necessary to prevent the volatilization and escape of phosphorus components. During the production process, the loss on ignition of the mixture should be controlled to ≤5% to prevent excessive gas generation at high temperatures, which would lead to excessive porosity of the ceramsite and insufficient fluorine curing.
[0042] Each batch of product must be tested for leaching toxicity, and the indicators must meet the requirements of the "Identification Standard for Hazardous Waste: Leaching Toxicity Identification" (GB5085.3-2007). The internal control standard for the product is: fluoride leaching concentration (in F... - The leaching concentration of heavy metals is ≤5 mg / L, the cyanide leaching concentration is ≤0.5 mg / L, and all heavy metal leaching indicators meet the standards. Simultaneously, the physical properties of the ceramsite (bulk density 500~700 kg / m³) are also satisfied. 3 The compressive strength is ≥1.0 MPa, and the water absorption rate is 8%~15%. The product particles are round and full spherical or near-spherical in shape, with good gradation.
[0043] If the fluoride leaching concentration of the product exceeds 10 mg / L, the amount of calcium supplement (high-calcium fly ash) can be increased to 15%~20%, and the product can be re-fired after being kept at 1150 ℃ for 30~45 min to make the fluoride leaching index of the product meet the standard.
[0044] Based on the above, the following description, in conjunction with the accompanying drawings and specific examples, further illustrates the method for preparing ceramsite by combining sludge from major repairs with industrial solid waste and the calcination of the ceramsite. The specific details are as follows.
[0045] Example 1 (1) Ingredients and Mixing: Weigh the following raw materials by mass percentage: 10% of the first-class major repair slag after water washing, 20% of the second-class major repair slag after water washing, 28% of the municipal sludge, 5% of the phosphogypsum, and 15% of the high-calcium fly ash. The particle size of each raw material is controlled as follows: ≤0.1 mm for the first-class major repair slag, 0.5~2 mm for the second-class major repair slag, ≤0.15 mm for the municipal sludge, and ≤0.075 mm for both the phosphogypsum and the high-calcium fly ash. Mix the above raw materials thoroughly and adjust the moisture content of the mixture to 12%~15%.
[0046] (2) Core-shell structure spheroidization: Using the second type of overhaul slag particles as the core and the remaining mixed powder as the shell, raw material spheres with a particle size of 6~12 mm and uniform strength are prepared by rolling granulation, and unqualified particles with irregular shape, cracks and insufficient strength are removed.
[0047] (3) Segmented high-temperature sintering: Qualified raw material balls are sent into the sintering kiln and subjected to thermal treatment in sequence, including drying at 200 ℃ for 30 min, preheating at 500 ℃ for 20 min, and holding at 1150 ℃ for 15 min. Then, they are naturally cooled to room temperature with the kiln to obtain finished lightweight ceramsite.
[0048] (4) Product test results: The bulk density of the ceramsite produced in this embodiment is 620 kg / m³. 3 The cylinder compressive strength is 1.3 MPa, and the fluorine leaching concentration is 3.78 mg / L, which is far below the limit of 100 mg / L; the heavy metal leaching indicators all meet the requirements of GB 5085.3-2007.
[0049] Example 2 (1) Batching and mixing: Weigh each raw material precisely according to the mass percentage: 7% of the first type of major repair slag after water washing, 20% of the second type of major repair slag after water washing, 22% of municipal sludge, 6.5% of phosphogypsum, and 16% of high-calcium fly ash. The proportion of each raw material meets the system molar ratio Ca:P:F=18:2:1, which can stably generate fluorapatite and realize the chemical mineralization and fixation of fluorine in solid waste.
[0050] All raw materials undergo strict particle size pretreatment: First-class overhaul slag is finely ground to a particle size ≤0.1mm; second-class overhaul slag is crushed and screened to precisely control the particle size range of 0.5~2 mm; municipal sludge is dried and pulverized to a particle size ≤0.15 mm; phosphogypsum and high-calcium fly ash are both ground to a particle size ≤0.075 mm, with phosphogypsum achieving a 200-mesh passing rate ≥90%, ensuring uniform material dispersion. The selected high-calcium fly ash contains 22.5% CaO, meeting the requirement of ≥20%.
[0051] Pretreated first-type overhaul slag, phosphogypsum, high-calcium fly ash, and municipal sludge were simultaneously fed into the mill for mixing to enhance the contact effect of raw material particles and obtain a uniformly mixed powder. Water was added to the mixed powder to adjust the initial moisture content, controlling it to 14%.
[0052] (2) Core-shell structure pelletizing: Using uniformly sized second-class overhaul slag particles as the rigid core and the remaining uniformly mixed powder as the coating shell, raw material pellets with a particle size of 6~12 mm, regular shape, dense structure, and uniform strength are prepared by vertical disc rolling granulation. After granulation, the raw material pellets are dried at 110 ℃ until the moisture content of the raw material pellets is ≤3% to avoid defects such as bursting, cracking, and bubbling during high-temperature sintering. At the same time, irregular, cracked, and loose unqualified raw material pellets are removed manually and by screening to ensure the uniform quality of the raw material pellets entering the kiln.
[0053] (3) Segmented high-temperature sintering: The qualified dried raw material pellets are sent into a rotary sintering kiln and thermally treated using a segmented gradient heating process. The specific sintering parameters are: constant temperature drying at 200 ℃ for 30 min to completely remove residual free moisture from the raw material pellets; heating to 500 ℃ for constant temperature preheating for 20 min to decompose the organic matter in the sludge, remove the crystal water from the raw materials, and stabilize the structure of the green body; continuing to heat to 1150 ℃ for constant temperature firing for 15 min to promote the solid-phase reaction of the raw materials, generate a stable crystalline phase of fluorapatite, and solidify heavy metals and fluoride ions; after sintering, the pellets are naturally cooled to room temperature with the kiln to obtain high-performance environmentally friendly lightweight ceramsite finished products.
[0054] (4) Product test results: The finished ceramic particles prepared in this embodiment have a dense structure, regular appearance, no obvious pores or cracks, and excellent lightweight and high strength properties. The leaching toxicity test results show that the fluorine leaching concentration is 2.26 mg / L, which is far below the limit of 100 mg / L specified in GB5085.3-2007, and the leaching concentrations of various heavy metals are all lower than the standard limits.
[0055] The ceramsite prepared by this invention was observed and analyzed, specifically including: Figure 3 The appearance of the ceramsite after firing in this embodiment is shown. For example... Figure 3 As shown, the ceramsite is nearly ellipsoidal in shape, with a rough surface and uniformly distributed micropores. The particles are regular in shape and uniform in size, exhibiting the typical appearance characteristics of lightweight ceramsite.
[0056] Figure 4 The microstructure of the ceramsite after firing in this embodiment is shown. For example... Figure 4 As shown, the ceramsite has a well-developed porous structure with interconnected and uniformly distributed pores and rough pore walls, which provides a large specific surface area, thus facilitating its application in landscaping, ecological filter media, and other fields. Figure 5 The chemical composition of the ceramsite after firing in this embodiment is shown. For example... Figure 5 As shown, ceramsite belongs to a typical SiO2-Al2O3-CaO-FeO multi-component oxide system, with its chemical composition mainly consisting of SiO2, CaO, Al2O3, and FeO, and containing small amounts of fluxing or auxiliary components such as MgO, K2O, and ZnO. This compositional characteristic indicates that the silicate-aluminate components in high-calcium fly ash and overhaul slag react fully at high temperatures to form stable silicate and aluminate mineral phases, providing a solid phase basis for the effective solidification of heavy metals and fluorine elements.
[0057] In summary, this invention uses aluminum electrolysis overhaul slag as the main raw material, and combines it with various industrial solid wastes such as municipal sludge, phosphogypsum, and high-calcium fly ash to prepare lightweight ceramsite. This invention is particularly suitable for environmentally friendly ceramsite products that require moderate compressive strength, focus on efficient solidification of harmful elements and co-processing of multi-source solid waste, and can be widely used in landscaping, lightweight filling, and ecological filter media.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A type of ceramsite produced by calcining sludge and industrial solid waste from overhaul slag, characterized in that... It consists of the following raw materials by weight percentage: After water washing, the first type of major repair waste is 8%~15%, the second type of major repair waste is 15%~25%, municipal sludge is 20%~35%, phosphogypsum is 5%~8%, and high-calcium fly ash is 10%~20%; The molar ratio of calcium, phosphorus, and fluorine in the raw material system is controlled as Ca:P:F = (15~20):2:
1.
2. The ceramsite according to claim 1, characterized in that, The ceramsite has a core-shell structure. The core is the second type of overhaul slag particles after water washing, and the shell is a sintered dense layer containing a chemically mineralized solid fluorine phase composed of fluorapatite and a glassy physical encapsulation phase.
3. The ceramsite according to claim 1, characterized in that, The first type of overhaul slag after water washing is cathode carbon block edge material and / or ramming material, with a particle size ≤0.1 mm, calorific value ≥1000 kcal / kg, total fluorine ≤0.5%, soluble fluorine ≤0.1%, and cyanide ≤5 mg / L; The second type of overhaul slag after water washing is an impermeable material and / or refractory brick, with a particle size of 0.5~2 mm, total fluorine ≤0.8%, and dissolved fluorine ≤0.2%; The particle size of the municipal sludge is ≤0.15 mm; The particle size of the phosphogypsum is ≤0.075 mm; The high-calcium fly ash contains ≥20% calcium oxide and has a particle size ≤0.075 mm.
4. A method for preparing ceramsite by calcining sludge and industrial solid waste using overhaul slag as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Preparation of matrix powder: Weigh the first type of major repair slag after water washing, municipal sludge, phosphogypsum and high calcium fly ash according to the ratio, mix and homogenize them to obtain matrix powder; S2, Core-shell gradient granulation: Using the second type of overhaul slag particles after water washing as the core, after wetting with water spray, the matrix powder obtained in step S1 is added to the rolling granulator, so that the matrix powder coats the surface of the core to form green pellets with a core-shell structure, and dried to a moisture content ≤3%; S3. High-temperature sintering: The green pellets dried in step S2 are sent into a kiln and subjected to thermal treatment in sequence through a preheating section, a medium-temperature reaction section, a high-temperature sintering section and a cooling section to obtain the ceramsite.
5. The method according to claim 4, characterized in that, In step S1, the moisture content of the matrix powder is controlled as follows: 12%~15% in summer and 15%~18% in winter; the mixing and homogenization time is 10~15 min.
6. The method according to claim 4, characterized in that, In step S2, the particle size of the green pellets is 6~12 mm; the drying operation adopts a mesh belt dryer, with two-stage temperature control: the first stage is dried at 105 ℃ for 25 min, and the second stage is dried at 120 ℃ until the moisture content is ≤2.5%.
7. The method according to claim 4, characterized in that, In step S3: The preheating section heats up to 100-300°C at a rate of 5-8°C / min to slowly remove water of crystallization and organic matter, preventing premature volatilization of fluorine. The intermediate-temperature reaction section involves oxidation at 600–900 °C for 40–60 min to promote Ca oxidation. 2+ and Combined, a fluorapatite precursor is initially generated; The high-temperature sintering section is heated to 1100-1200 ℃ at a rate of 30-40 ℃ / min to form a dense glassy phase, in which fluorapatite is fully crystallized and the fluorine solidification rate is ≥98%. The cooling section involves first slowly cooling the material inside the kiln to 550~600 ℃ at a rate of ≤10 ℃ / min, and then allowing it to be discharged and naturally cooled to room temperature to avoid sudden cooling cracking and shell shedding.
8. The method according to claim 4 or 7, characterized in that, In the high-temperature sintering section, a weak oxidizing atmosphere is used in the kiln, with an oxygen content of 2% to 5%, to avoid the decomposition and volatilization of fluorides caused by reduction. When the total fluorine content in the raw materials is too high, the firing temperature of the high-temperature sintering section is increased by 30 to 50 °C, and the holding time is extended by 5 to 8 minutes.
9. The method according to claim 4, characterized in that, The method also includes installing alkali spraying and bag filter equipment at the kiln tail to control fluorine emissions ≤3 mg / m³. 3 .
Citation Information
Patent Citations
Formula and process method for preparing ceramsite by using overhaul slag
CN113173777A
Process for preparing cement from aluminum electrolysis overhaul slag and waste anti-seepage material lithium extraction residue
CN121672962A
Method for synergistically preparing high-performance adsorption material from electrolytic aluminum overhaul slag and red mud and application of high-performance adsorption material
CN121847079A